PENGARUH METODE EKSPERIMEN TERHADAP KETERAMPILAN PROSES SAINS PADA MATERI PERUBAHAN WUJUD ZAT DI SEKOLAH DASAR - Marsha Isnaini Ananti; Abdillah, Mochamad Ilham; Syahira Ramadhini; Afrida Laily Aliandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the experimental method in improving students’ science process skills (SPS), particularly in elementary school science education on the topic of changes in the state of matter. The issue addressed is the low level of students’ scientific skills due to the dominance of conventional teaching methods that do not sufficiently engage students. This study employs the Systematic Literature Review (SLR) method by examining various national and international articles published between 2022 and 2026. Data collection was conducted through documentation, while data analysis was performed qualitatively by identifying patterns, trends, and research gaps. The results indicate that experiment-based learning consistently exerts a positive and significant influence on the improvement of students’ SPS, encompassing observation skills, classification, hypothesis formulation, experiment execution, and data analysis. Various approaches, such as inquiry-based learning, STEM, guided discovery, and project-based learning, also support the development of higher-order thinking skills and conceptual understanding. However, some studies still have limitations in their design and implementation, such as the absence of a control group and limited integration of technology. Overall, the experimental method has proven effective in developing scientific skills and fostering meaningful learning when supported by appropriate instructional design.